1996
DOI: 10.1074/jbc.271.26.15675
|View full text |Cite
|
Sign up to set email alerts
|

A Major Tyrosine-phosphorylated Protein of Trypanosoma brucei Is a Nucleolar RNA-binding Protein

Abstract: We have previously identified a set of tyrosine-phosphorylated proteins with apparent molecular masses of 44-46 kDa as some of the major tyrosine phosphorylated species in the protozoan parasite Trypanosoma brucei. We now show that these molecules, herein named Nopp44/46, are localized in the nucleolus. Using monoclonal antibodies, we have isolated Nopp44/46 cDNA clones from expression libraries. Sequence analysis reveals that the predicted amino acid sequence of the molecule is composed of an N-terminal uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Nopp44/46 localises to the nucleolus and in vitro binding experiments have demonstrated that this protein is capable of binding nucleic acids with a preference for poly (U). 23 Therefore, the function of RBM6 might still be comparable with the function of RBM5.…”
Section: Discussionmentioning
confidence: 97%
“…Nopp44/46 localises to the nucleolus and in vitro binding experiments have demonstrated that this protein is capable of binding nucleic acids with a preference for poly (U). 23 Therefore, the function of RBM6 might still be comparable with the function of RBM5.…”
Section: Discussionmentioning
confidence: 97%
“…NOPP44/46 Tyr 181 , however, was not identified, likely due to experimental limitations of that study. By immunofluorescence, phosphotyrosine proteins mostly associated with the cytoskeleton and the nucleolus, which is also the site of NOPP44/46 (32). A physiological interaction between TbPTP1 and NOPP44/46 would require cellular co-localization, and consistent with this tenet, TbPTP1 was found to associate with the cytoskeletal and nuclear fractions (10).…”
Section: Data Collectionmentioning
confidence: 90%
“…For immunoprecipitation from T. brucei, cells containing inducible expression cassettes were treated with Tet for 16-24 hours and sample lysates prepared as described [31]. Immunoprecipitations were performed as described above, using 10 8 cells per reaction.…”
Section: Immunological Methodsmentioning
confidence: 99%